2017
DOI: 10.1111/1750-3841.13815
|View full text |Cite
|
Sign up to set email alerts
|

Singlet Oxygen Detection Using Red Wine Extracts as Photosensitizers

Abstract: Moderate consumption of red wine provides beneficial effects to health. This is attributed to polyphenol compounds present in wine such as resveratrol, quercetin, gallic acid, rutin, and vanillic acid. The amount of these antioxidants is variable; nevertheless, the main beneficial effects of red wine are attributed to resveratrol. However, it has been found that resveratrol and quercetin are able to photosensitize singlet oxygen generation and conversely, gallic acid acts as quencher. Therefore, and since resv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…The use of phenols, both condensed and hydrolyzable tannins, is an acknowledged approach to limit some wine faults, such as the appearance of LST [ 9 ], thanks to their antioxidant properties as well as their ability in quenching the singlet oxygen [ 26 , 27 ]. During winemaking, tannins can be added on grape musts during pre-fermentative step or on finished wines as clarifying or stabilization agents.…”
Section: Resultsmentioning
confidence: 99%
“…The use of phenols, both condensed and hydrolyzable tannins, is an acknowledged approach to limit some wine faults, such as the appearance of LST [ 9 ], thanks to their antioxidant properties as well as their ability in quenching the singlet oxygen [ 26 , 27 ]. During winemaking, tannins can be added on grape musts during pre-fermentative step or on finished wines as clarifying or stabilization agents.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, its low limit of detection (LOD) of about 2.8 nmol/L, and the intense red shift of the phosphorescence signal allows the investigation of very low yields of 1 O 2 produced by photo-sensitizers [59]. In addition to common spectroscopic techniques mentioned above, one can also use more complex detection methods, depending on the available equipment like electron paramagnetic resonance spectroscopy (EPR) [60], nuclear magnetic resonance spectroscopy (NMR) [61] or liquid chromatography [62]. Especially EPR is a useful technique in detecting and identifying ROS, however, it is not a standard technique in the pharmaceutical industry.…”
Section: Singlet Oxygen ( 1 O2)mentioning
confidence: 99%
“…From the applicative point of view, it would be interesting to understand whether different categories of BENs and CHAs could be used successfully in real wines. Besides white wines, which are commonly preferred for RF studies because of being more subjected to light-struck fault, red wines represent an interesting case of study because, as reported by Lagunes et al (2017), their extracts could act as photosensitizer if exposed to light, generating 1 O 2 , which in turn is able to oxidize other compounds. Moreover, polyphenols make more complex the removal of RF because of the high affinity of phenols to CHAs (Lisanti et al, 2017).…”
Section: Bentonite's Protein Adsorption Trialmentioning
confidence: 99%